Identification and Antimicrobial Susceptibility Patterns of Staphylococcus aureus in Mastitic Cases from Namakkal District - R. Navaneethan; S. Saravanan (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
The study was conducted to identify the prevalence of Staphylococcal mastitis in bovines from Namakkal region and the therapeutic response of antibiotics to Staphylococci by assessing the antibiotic sensitivity pattern in clinical settings. Milk samples (n= 241) were collected from clinical and subclinical mastitic cows which were brought to teaching veterinary clinical complex (TVCC), Veterinary College and Research Institute (VC&RI), Namakkal, Tamil Nadu and subjected to isolation on mannitol salt agar, Gram’s staining and confirmation by polymerase chain reaction (PCR) using specific primers. The prevalence of Staphylococcus aureus at cow level was 61.5 and 57.4 per cent in clinical and subclinical cases, respectively, and at quarter level was 58.8 and 57.4 per cent in the clinical and subclinical cases, respectively. Antibiotic sensitivity pattern revealed a high sensitivity to enrofloxacin (100.0%) and a high resistance to methicillin (100.0%) by S. aureus isolates, and multidrug resistance by S. aureus isolates was also observed. Though enrofloxacin was found to be very effective in therapeutic management of most staphylococcal mastitis cases, antibiogram of milk sample from each mastitis cow is essential to monitor the development of resistance of Staphylococcus aureus in clinical or subclinical mastitis to the range of antibiotics commonly used. This would help in the early treatment of mastitis with sensitive antibiotics and prevent the case entering into the chronic stage, failure of treatment and loss of the value of cow.